K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

NM
3 tháng 11 2021

ta có 

\(cosa=sin52^0=cos\left(90^0-52^0\right)=cos\left(38^0\right)\)

vậy \(a=38^0\)

\(A=\dfrac{\sqrt{2}}{2}\cdot\cos^252^0+\dfrac{\sqrt{2}}{2}\cdot\sin^252^0\)

\(=\dfrac{\sqrt{2}}{2}\left(\cos^252^0+\sin^252^0\right)\)

\(=\dfrac{\sqrt{2}}{2}\)

12 tháng 8 2020

Chú ý 2 điều: \(\cos45^o=\sin45^o=\frac{\sqrt{2}}{2}\) và \(\cos^2a+\sin^2a=1\)

Do đó: 

a) \(A=\cos^252^o.\frac{\sqrt{2}}{2}+\sin^252^o.\frac{\sqrt{2}}{2}=\frac{\sqrt{2}}{2}\left(\cos^252^o+\sin^252^o\right)=\frac{\sqrt{2}}{2}.1=\frac{\sqrt{2}}{2}\)

b) \(B=\frac{\sqrt{2}}{2}.\cos^247^o+\frac{\sqrt{2}}{2}.\sin^247^o=\frac{\sqrt{2}}{2}\left(\cos^247^o+\sin^247^o\right)=\frac{\sqrt{2}}{2}.1=\frac{\sqrt{2}}{2}\)

\(A=\cos^252^0\cdot\sin45^0+\sin^252^0\cdot\cos45^0\)

\(=\dfrac{\sqrt{2}}{2}\left(\cos^252^0+\sin^252^0\right)=\dfrac{\sqrt{2}}{2}\)

14 tháng 7 2016

Ta có: \(\frac{cosa+sina}{cosa-sina}=\frac{\frac{cosa}{cosa}+\frac{sina}{cosa}}{\frac{cosa}{cosa}-\frac{sina}{cosa}}=\frac{1+tana}{1-tana}=\frac{1+\frac{1}{3}}{1-\frac{1}{3}}=2\)

             

a: \(=\dfrac{\sqrt{2}}{2}\left(cos^252^0+sin^252^0\right)=\dfrac{\sqrt{2}}{2}\)

b: \(=\dfrac{\sqrt{2}}{2}\left(cos^247^0+sin^247^0\right)=\dfrac{\sqrt{2}}{2}\)

3 tháng 10 2017

sin 39 ° 13 '  ≈ 0,6323     cos 52 ° 18 '  ≈ 0,6115

tg 13 ° 20 '  ≈ 0,2370     cotg 10 ° 17 '  ≈ 0,5118

sin 45 °  ≈ 0,7071     cos 45 °  ≈ 0,7071